2021
DOI: 10.3390/biom11050695
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Gut Microbiome are Associated with Prognosis of Hypertriglyceridemia-Associated Acute Pancreatitis

Abstract: Hypertriglyceridemia-associated acute pancreatitis (HTGAP) is linked with increased severity and morbidity. Intestinal flora plays an important role in the progression of acute pancreatitis (AP). However, pathogenetic association between gut microbiota and HTGAP remains unknown. In this study, we enrolled 30 HTGAP patients and 30 patients with AP that is evoked by other causes. The V3–V4 regions of 16S rRNA sequences of the gut microbiota were analyzed. Clinical characteristics, microbial diversity, taxonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
(62 reference statements)
1
27
0
Order By: Relevance
“…At the phylum level, the abundance of Proteobacteria and Actinobacteria is elevated in the intestine of SAP patients, whereas the abundance of Firmicutes and Bacteroides is decreased. At the genus level, SAP patients show a significant increase in the abundance of facultative anaerobic bacteria in the intestine, such as Escherichia , Enterococcus , Enterobacter , Streptococcus , etc., with a decrease in Bacteroides , Bifidobacterium , and Blautia , etc., and the SAP animal models show similar results ( 2 , 16 18 , 20 , 21 ). Furthermore, analyses of the bacterial community reveal that the most noticeable differences in species abundance are located in the cecum and colon ( 24 ).…”
Section: Dysbiosis Of Intestinal Microbiota In Sapsupporting
confidence: 60%
“…At the phylum level, the abundance of Proteobacteria and Actinobacteria is elevated in the intestine of SAP patients, whereas the abundance of Firmicutes and Bacteroides is decreased. At the genus level, SAP patients show a significant increase in the abundance of facultative anaerobic bacteria in the intestine, such as Escherichia , Enterococcus , Enterobacter , Streptococcus , etc., with a decrease in Bacteroides , Bifidobacterium , and Blautia , etc., and the SAP animal models show similar results ( 2 , 16 18 , 20 , 21 ). Furthermore, analyses of the bacterial community reveal that the most noticeable differences in species abundance are located in the cecum and colon ( 24 ).…”
Section: Dysbiosis Of Intestinal Microbiota In Sapsupporting
confidence: 60%
“…Evidence showed that Enterococcus faecalis disturbed the lipid metabolism (Huang et al, 2018;. Hu X et al revealed that a higher abundance of Enterococcus had a closely related to poor prognosis of hypertriglyceridemia-related acute pancreatitis leading to poor prognosis in hypertriglyceridemia patients (Hu et al, 2021), suggesting that Enterococcus might be involved in the prognosis of hyperlipidemic stroke patients. In this study, there was a lower relative abundance of SCFAs-producing bacteria in POAH group, such as Lachnospiraceae, Faecalibacterium, Rothia and Butyricicoccus.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the intestinal barrier is a factor that exacerbates the inflammatory response to SIRS [ 27 ]. After intestinal barrier damage, the most direct consequence may be the “second strike” of intestine-derived endotoxins entering the circulation and lungs through the portal vein or mesenteric lymphatic system [ 28 , 29 ]. On the other hand, SIRS may be promoted by exosomes released from the injured gut during AP.…”
Section: Exosomes and Ap-associated Alimentioning
confidence: 99%